2017
DOI: 10.2147/jbm.s134932
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia and its associated factors among pregnant women receiving antenatal care at Aymiba Health Center, northwest Ethiopia

Abstract: IntroductionAnemia is a global public health problem in both developing and developed countries; ~1.62 billion people suffer from anemia, and pregnant women are the most susceptible to it. The main aim of the present study was to assess the prevalence of anemia and associated risk factors among pregnant women receiving antenatal care at Aymiba Health Center, northwest Ethiopia.Methods and materialsAn institution-based cross-sectional study was conducted at Aymiba Health Center from January to March 2015. Hemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
4
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 18 publications
7
52
4
4
Order By: Relevance
“…According to the World Health Organization classification, the prevalence of anemia among pregnant women in this study was a severe public health problem [17] [28] [29]. The prevalence determined in this study area was comparable with other studies reported in different countries: Bangladesh (59%), Bhutan (59%), and Sri Lanka (60%) [25], China (58.6%) [18], Malaysia (57.4%) [27]; higher than Republic in Korea (30.2%), South Africa (19.7%) [15], in rural area of Southern Ethiopia (29%); and lower than India (87.2%), Pakistan (90.5%) [27] and Nepal (73%) [9]. Socio-demographic factors are associated with anemia among pregnant women [22].…”
Section: Discussionsupporting
confidence: 83%
“…According to the World Health Organization classification, the prevalence of anemia among pregnant women in this study was a severe public health problem [17] [28] [29]. The prevalence determined in this study area was comparable with other studies reported in different countries: Bangladesh (59%), Bhutan (59%), and Sri Lanka (60%) [25], China (58.6%) [18], Malaysia (57.4%) [27]; higher than Republic in Korea (30.2%), South Africa (19.7%) [15], in rural area of Southern Ethiopia (29%); and lower than India (87.2%), Pakistan (90.5%) [27] and Nepal (73%) [9]. Socio-demographic factors are associated with anemia among pregnant women [22].…”
Section: Discussionsupporting
confidence: 83%
“…Di negara-negara berkembang, penyebab anemia selama kehamilan adalah multifaktorial, termasuk kekurangan gizi zat besi, folat, dan vitamin B12 dan juga penyakit parasit, seperti malaria dan infeksi parasit usus. Kontribusi relatif dari masing-masing faktor ini terhadap anemia selama kehamilan sangat bervariasi berdasarkan lokasi geografis, musim, dan praktik diet (Asrie, 2017).…”
Section: Pendahuluan *unclassified
“…It was lower than the prevalence of iron deficiency anaemia in the third trimester in one of the study sites of our study in 2016 [24], probably due to optimized intake of iron and the management of underlying diseases like malaria at the end of third trimester of pregnancy as it is the case in our study, as compared to the whole third trimester considered in that one. Fikir also identified Intestinal helminth infection as a cause of anaemia [25].…”
Section: Prevalence Of Anaemia On Admissionmentioning
confidence: 99%